BaxSr1−xTiO3 sensing membrane in electrolyte-insulator-semiconductor structure with rapid thermal annealing in N2 ambient. (June 2017) - Kao, Chyuan-Haur; Chiu, Wang Ting; Chen, Yi Cian; Yang, Luo; Tsai, Shin Chieh; Chang, Ting Wei; Tsai, Ching-Tsan; Lin, Chan-Yu; Chen, Hsiang
Abstract: Ion-sensitive field - effect transistor (ISFET) biosensors were fabricated with a pH-sensitive Bax Sr1−x TiO3 membrane on silicon substrates in an Electrolyte-Insulator-Semiconductor (EIS) structure. To investigate the effects of annealing in N2 ambient, multiple material analyses including XRD and AFM were performed. Results indicate that the annealing treatment might deteriorate the crystallization. Therefore, the sensing behaviours in terms of sensitivity, linearity, hysteresis effects, and drift rates might be worsened. In this research, Bax Sr1−x TiO3 membranes in an EIS structure with a high sensitivity and linearity were made. However, owing to its special and complicated structures, high-temperature thermal annealing was not suitable for the Bax Sr1−x TiO3 membrane to further boost its sensing capability. Highlights: Bax Sr1−x TiO3 EIS biosensors have been fabricated. Multiple Material analysis and sensing tests have been performed. Material quality might be deteriorated by annealing. The pH sensing capability has been detected.